Neutron and X-ray Spectroscopy - Hippert, Françoise; Geissler, Erik.; Hodeau, Jean Louis; Lelièvre-Berna, Eddy.; Regnard, Jean-René.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2006)
Neutron and X-Ray Spectroscopy delivers an up-to-date account of the principles and practice of inelastic and spectroscopic methods available at neutron and synchrotron sources, including recent developments. The chapters are based on a course of lectures and practicals (the HERCULES course) delivered to young scientists who require these methods in their professional careers. Each chapter, written by a leading specialist in the field, introduces the basic concepts of the technique and provides an overview of recent work. This volume, which focuses on spectroscopic techniques in synchrotron radiation and inelastic neutron scattering, will be a primary source of information for physicists, chemists and materials scientists who wish to acquire a basic understanding of these techniques and to discover the possibilities offered by them. Emphasizing the complementarity of the neutron and X-ray methods, this tutorial will also be invaluable to scientists already working in neighboring fields who seek to extend their knowledge.
X-ray Spectroscopy -- Fundamentals of X-ray Absorption and Dichroism: The Multiplet Approach -- Multiple Scattering Theory Applied to X-Ray Absorption Near-Edge Structure -- X-ray Magnetic Circular Dichroism -- Extended X-Ray Absorption Fine Structure -- Inelastic X-Ray Scattering from Collective Atom Dynamics -- Photoelectron Spectroscopy -- Anomalous Scattering and Diffraction Anomalous Fine Structure -- Soft X-Ray Photoelectron Emission-Microscopy (X-PEEM) -- X-Ray Intensity Fluctuation Spectroscopy -- Vibrational Spectroscopy at Surfaces and Interfaces Using Synchrotron Sources and Free Electron Lasers -- Neutron Spectroscopy -- Inelastic Neutron Scattering: Introduction -- Three-Axis Inelastic Neutron Scattering -- Neutron Spin Echo Spectroscopy -- Time-of-Flight Inelastic Scattering -- Neutron Backscattering Spectroscopy -- Neutron Inelastic Scattering and Molecular Modelling.
Keywords: Solid state physics; Spectroscopy; Microscopy; Condensed matter; Materials science; Materials—Surfaces.; Thin films; Mineralogy; Solid State Physics; Spectroscopy and Microscopy; Condensed Matter Physics; Materials Science, general; Surfaces and Interfaces, Thin Films; Mineralogy